THE EFFECT OF CIRCULATING FAN AND NATURAL VENTILATION ON THE THERMAL COMFORT PERFORMANCE IN A BUILDING IN SOUTHEAST SULAWESI - Aditya Rachman; Aspin Aspin; Siti Belinda (Jurusan Teknik Mesin, Universitas Halu Oleo, 2014)
The unbalance on the supply and demand on the energy has an impact on the escalating energy price and potentially impedes the development. One of the power demands comes from the energy utilization in the building sector, in which the cooling system is among them. The application of the air conditioning based on the refrigerator system is obviously consuming much energy in the building. Thus reducing the role of this power consumed cooling system is so imperative. To apply the circulating fan or to employ the natural ventilation are among the alternative approaches to make a building cooler, without much consuming energy. The aim of this study is to investigate the effect the circulating fan and the natural ventilation, on the temperature and the humidity in a building in Southeast Sulawesi, a region with its high daily solar radiation. It conducts an experiment on a building model incorporated with the ventilation and the circulating fan. The result shows that by incorporating these alternative cooling devices, the temperatures in the building can be lower than that of a closed building (no fan and no ventilation). The magnitude in the decreasing on the temperature for the building with circulating fan is higher than that of the ventilation. Another result on the investigation shows that the relative humidity in the building with the circulating fan or the ventilation is relatively higher than that of the closed building.